The Urgency of Education in Supporting the Country's Eco-nomic Development Through the Human Capital Theory Approach - Isma Yulia Sofiani; Miftahus Surur; May Husnul Khotimah; Sugianto Sugianto; Ibrahim Mallam Fali (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article raises the academic issue of the low contribution of education quality to economic development in several developing countries, including Indonesia. This problem arises due to limited investment in developing quality human resources. Education plays a strategic role in shaping the intellectual capacity, skills, and productivity of the workforce, which are the foundation of sustainable economic growth. The purpose of this study is to analyze the urgency of education in supporting economic development through the perspective of Human Capital Theory, which emphasizes the importance of investing in people as a primary development asset. This study uses a desk study method by reviewing various academic literature, previous research results, and reports from international institutions regarding the relationship between education and economic growth. The results show that education plays a crucial role in driving economic and social development through the development of competent human resources. Based on human capital theory, investment in education can improve individual capabilities and societal welfare. Developed countries such as Finland, Japan, and Singapore have successfully demonstrated that large budget allocations to the education sector can sustainably increase economic productivity. However, developing countries and Muslim countries still face obstacles such as unequal access, limited facilities, and low teaching quality. Meanwhile, education in Muslim countries needs to be strengthened through curriculum reform and improved teaching quality to produce a skilled and globally competitive generation.